2019
DOI: 10.1051/e3sconf/20199903011
|View full text |Cite
|
Sign up to set email alerts
|

Modelling transportation of desert dust to the South Caucasus using WRF Chem model

Abstract: The problem of the ongoing climate change resulting from natural and growing anthropogenic factors acquires a particular importance for the territory of the Caucasus. Dust aerosol represent one of the main pollutants on the territory of Georgia and impact on regional climate. In this study, the WRF Chemistry model with dust module is used to study transportation of dust to the territory of the South Caucasus from the Sahara and Sahel in Africa, Arabian and ar-Rub’ al-Khali deserts located in the Middle East, K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Roberts et al, 2008;Israelevich et al, 2012;Bout-Roumazeilles et al, 2013), significant amounts of dust can be transported from the Sahara desert by the aforementioned southerly winds. Moreover, the transportation of dust to the eastern part of the Black Sea is associated with easterly /southeasterly winds related to the lowand mid-tropospheric flows from the Caspian -Central Asia regions in the east and warm advection from the Middle East in the south (Davitashvili, 2019). In general, the dust transport occurs in the form of "pulses", and the annual dust flux can be controlled by a few episodes, with several researchers (e.g.…”
Section: Mediterranean and Black Sea Marine Systemmentioning
confidence: 99%
“…Roberts et al, 2008;Israelevich et al, 2012;Bout-Roumazeilles et al, 2013), significant amounts of dust can be transported from the Sahara desert by the aforementioned southerly winds. Moreover, the transportation of dust to the eastern part of the Black Sea is associated with easterly /southeasterly winds related to the lowand mid-tropospheric flows from the Caspian -Central Asia regions in the east and warm advection from the Middle East in the south (Davitashvili, 2019). In general, the dust transport occurs in the form of "pulses", and the annual dust flux can be controlled by a few episodes, with several researchers (e.g.…”
Section: Mediterranean and Black Sea Marine Systemmentioning
confidence: 99%
“…According to statistics of the National Environmental Agency (NEA) of Georgia, the frequency of natural disasters in recent decades has increased significantly, namely heavy rains increased with dramatic consequences, which undoubtedly is associated with climate change [3]. Heavy rains, hail, floods and drought are the main climatological hazards for the country [5][6][7]. It is reported that floods kills more people, but droughts affect far more number of people and causes more economic damage in Georgia.…”
Section: Icies'2020mentioning
confidence: 99%
“…For example, a severe drought in 2000 affected about 700,000 people and caused damage of 5.6% of GDP due to its impact on agriculture and hydropower production [8]. The same applies to natural disasters such as landslides, avalanches and tornadoes indicating climate change [3,6,7]. During the last four decades the number of natural hazards in comparison to 60th years of the last century has increased about three times and as a consequence economic expenses have increased eight times [2,9].…”
Section: Icies'2020mentioning
confidence: 99%
See 2 more Smart Citations